2021
DOI: 10.3390/ijms222212333
|View full text |Cite
|
Sign up to set email alerts
|

NGAL as a Potential Target in Tumor Microenvironment

Abstract: The signaling network between cancer and stromal cells plays a crucial role in tumor microenvironment. The fate of tumor progression mainly depends on the huge amount of information that these cell populations exchange from the onset of neoplastic transformation. Interfering with such signaling has been producing exciting results in cancer therapy: just think of anti-PD-1/anti-PD-L1/anti-CTLA-4 antibodies that, acting as immune checkpoint inhibitors, interrupt the inhibitory signaling exerted by cancer cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 108 publications
0
21
0
Order By: Relevance
“…Interestingly, several studies reported that TME regulates the expression of LCN2, SLC22A17, and MMP9, which, in turn, modify the TME dynamism demonstrating a reciprocal modulation (Kessenbrock et al, 2010;Candido et al, 2016a;Wei et al, 2020;Crescenzi et al, 2021). This crosstalk is mediated Frontiers in Cell and Developmental Biology frontiersin.org by several chemokines, cytokines, and fibrillar proteins that activate the transcription of LCN2, SLC22A17, and MMP9 (Chinni et al, 2006;Iannetti et al, 2008;Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several studies reported that TME regulates the expression of LCN2, SLC22A17, and MMP9, which, in turn, modify the TME dynamism demonstrating a reciprocal modulation (Kessenbrock et al, 2010;Candido et al, 2016a;Wei et al, 2020;Crescenzi et al, 2021). This crosstalk is mediated Frontiers in Cell and Developmental Biology frontiersin.org by several chemokines, cytokines, and fibrillar proteins that activate the transcription of LCN2, SLC22A17, and MMP9 (Chinni et al, 2006;Iannetti et al, 2008;Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, numerous studies have highlighted the role of TME in several cancer features, including survival, invasion, metastasis, immune escape, and drug resistance. In this context, the LCN2–SLC22A17–MMP9 (lipocalin 2—solute carrier family 22 member 17—matrix metallopeptidase 9) pathway contributes to the establishment and remodeling of TME, which is responsible for the tumor progression ( Kessenbrock et al, 2010 ; Crescenzi et al, 2021 ). For instance, the MMP9–NGAL complex is involved in the ECM degradation and chevage of some adhesion proteins, thus, promoting cell migration and invasion ( Candido et al, 2016a ; Huang, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…During hematopoiesis, immature (CD34 + ) bone marrow progenitor cells, granulocyte precursors, activated monocytes, macrophages and neutrophils express NGAL. In contrast, NGAL protein expression has never been reported in lymphocytes and plasmacytes (9)(10)(11)(12)(13). Circulating low levels of NGAL can be detected in the urine and blood of healthy people, possibly secreted by neutrophils and renal epithelial cells.…”
Section: Introductionmentioning
confidence: 93%
“…As a member of the lipocalin superfamily, neutrophil gelatinaseassociated lipocalin (NGAL), also called lipocalin 2 or 24p3, was first isolated as a 25 kDa glycoprotein covalently bound to matrix metalloproteinase 9 (MMP9) in neutrophils. NGAL has been initially classified as an acute phase protein, which is rapidly released, mainly from neutrophils, as a response to inflammation and tissue injury (9)(10)(11). Initially, NGAL was thought to be an antibacterial factor and a component of the innate immune system and present in a large variety of cell types including hemopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil gelatinase-associated lipocalin (NGAL) is one of the most recently intensively studied renal biomarkers that can indicate early structural damage and patient renal prognosis ( 79 ). It is a protein with a molecular weight of approximately 25 kDa that can exist as a monomer or form homodimers with MMP-9 with a molecular weight of approximately 46 kDa or heterodimers with a molecular weight of approximately 135 kDa and belongs to the lipocalin family, a group of small secreted proteins involved in the transport of small lipophilic molecules ( 80 ). It is a promising biomarker for tubulointerstitial lesions.…”
Section: Early Biomarkers Of Gout Kidney Injurymentioning
confidence: 99%